If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7x = 34 Solving 9 + -7x = 34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -7x = 34 + -9 Combine like terms: 9 + -9 = 0 0 + -7x = 34 + -9 -7x = 34 + -9 Combine like terms: 34 + -9 = 25 -7x = 25 Divide each side by '-7'. x = -3.571428571 Simplifying x = -3.571428571
| -6=3n+9 | | F(x)=2x^2-32 | | 0.75e-4=7 | | -9a^2=-8 | | 8x+2=3x-15 | | 16=10-x | | 10-5r=8 | | 0.75k-4=7 | | 4+3d=(-23) | | 3p+7=s | | 4y^2-16+12=0 | | 2(8v+8)=9(2v+3) | | -53=3+7x | | 3x-9=17-3x | | 4+3d=23 | | 2(8)-2x=10 | | 3t+10=58 | | 2x-41=x | | 3r+24=63 | | 9[e+3]=11e-13 | | 90=2x+3x-5 | | 47x+1=65x | | 2x-4(x+2)=-8+5x-33 | | 5+6*8+h=7*3+h | | 23-3m=5m+7 | | (2y^2+x)(y^2-7x)= | | (-1+6i)(3-5i)= | | 8[d+5]=12d-8 | | 3x-9=3(5-3x) | | 70-40+10x=12x+40-40 | | 3(x-3)-2(x+1)= | | 96t-16t^2-80=0 |